Fuzzy based hierarchical optimized approach with connectivity in WSN using multiple conflicting factors for application in the supervision of pipeline. Issue 1 (March 2021) - Rajpoot, Prince; Dwivedi, Pragya
Abstract: Wireless sensor network presents a real-time system different from its traditional infrastructure, which comprises of sensor nodes have limited computation, energy and storage space. The main issue of WSN is to maximize the network lifetime of WSN as sensor nodes began to die after a certain interval of time. To resolve this issue many algorithms have been proposed keeping clustering as the best solution. The best cluster head selection has extremely minimized energy consumption. We have worked on a hierarchical algorithm which deals with fuzzy logic approach rooted on four parameters- a) Delay, b) Connectivity to Sink, c) Average Lifetime of Member Nodes, d) Standard Deviation of Lifetime of Members. We have used these parameters for data communication regarding the hazardous activities in the pipelining like: leakage of gas, petrol etc. This algorithm is for low computational sensor networks in nature where we can't compute a lot. Connectivity confirms the effective data communication between CH to BS. We have shown a graphical rep The results and simulation depict the efficiency of the proposed algorithm with the base algorithm. A worthy increase in the existence of the network can be examined as compared to traditional ways of selecting the cluster head.